Protective Effectiveness of Long-Lasting Permethrin Impregnated Clothing Against Tick Bites in an Endemic Lyme Disease Setting: A Randomized Control Trial Among Outdoor Workers. Issue 5 (11th April 2020) - Mitchell, Cedar; Dyer, Megan; Lin, Feng-Chang; Bowman, Natalie; Mather, Thomas; Meshnick, Steven
Abstract: Tick-borne diseases are a growing threat to public health in the United States, especially among outdoor workers who experience high occupational exposure to ticks. Long-lasting permethrin-impregnated clothing has demonstrated high initial protection against bites from blacklegged ticks, Ixodes scapularis Say (Acari: Ixodidae), in laboratory settings, and sustained protection against bites from the lone star tick, Amblyomma americanum (L.) (Acari: Ixodidae), in field tests. However, long-lasting permethrin impregnation of clothing has not been field tested among outdoor workers who are frequently exposed to blacklegged ticks. We conducted a 2-yr randomized, placebo-controlled, double-blinded trial among 82 outdoor workers in Rhode Island and southern Massachusetts. Participants in the treatment arm wore factory-impregnated permethrin clothing, and the control group wore sham-treated clothing. Outdoor working hours, tick encounters, and bites were recorded weekly to assess protective effectiveness of long-lasting permethrin-impregnated garments. Factory-impregnated clothing significantly reduced tick bites by 65% in the first study year and by 50% in the second year for a 2-yr protective effect of 58%. No significant difference in other tick bite prevention method utilization occurred between treatment and control groups, and no treatment-related adverse outcomes were reported. Factory permethrin impregnation of clothing is safe and effective for the prevention of tick bites among outdoor workers whose primary exposure is to blacklegged ticks in the northeastern United States.